ANALISIS KEPATUHAN SUPERVISOR TERHADAP IMPLEMENTASI PROGRAM OCCUPATIONAL HEALTH & SAFETY (OHS) PLANNED INSPECTION DI PT. CCAI - Sarah, Dewi; Ekawati, Ekawati; Widjasena, Baju (Jurnal Kesehatan Masyarakat (Undip), 2015)
The Government has issued Regulation Legislation No. 50 Year 2012 on Health and Safety Management System (SMK3). CCAI is a company that has implemented SMK3. The application of the CCAI SMK3 supported by K3 program one of them is OHS Planned Inspection. This study aimed to analyze the implementation of Occupational Health & Safety (OHS) program Planned Inspection in CCAI. The subjects of this study amounted to five people as the main informants and 2 as an informant triangulation. The results showed key informants already knew this progrtam, goals, objectives, and program execution time. The attitude of key informants agreed with this program and in this  implementation need a good communication to superiors, as well as to the team below. The availability of facilities in the form is a checklist. The main informant had never been trained filling checklist. SOP that there has not been spread widely disseminated to all employees including key informants. Supervision only from an informant triangulation and has not from the respective. The results showed a less training and supervision provided by the OHS (Occupational Health Safety). This resulted in the knowledge and attitudes of employees is still low on the implementation of Planned Inspection program. CCAI need to provide training to fill the key informant checklist to improve the capability and compliance in conducting Planned Inspection program. Improve the surveilance and communication in the implementation of the program.